The longest ride [compact disc, unabridged] - Sparks, Nicholas (Hachette Audio, 2013)
In the tradition of his beloved first novel, The Notebook, #1 New York Times bestselling author Nicholas Sparks returns with the remarkable story of two couples whose parallel love stories intersect in profound and surprising ways.